Lin Shu, Inc. translation and the making of modern Chinese culture - Hill, Michael (Michael Gibbs) (New York : Oxford University Press, 2013)
Exploring the dynamic interactions between literary translation commercial publishing, and the politics of 'traditional' Chinese culture in the late 19th and early 20th centuries, this book traces how Lin Shu and a team of translators brought classic Western novels by Melville, Stowe, Dickens, and others to China.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Includes bibliographical references and index.
Keywords: Chinese language -- Translating -- History -- 19th century; Chinese language -- Translating -- History -- 20th century; Publishers and publishing -- China -- History -- 19th century; Publishers and publishing -- China -- History -- 20th century; China -- Civilization -- 19th century; China -- Civilization -- 20th century